Dynamic Governance in The Management of Kibitay Urban Forest in Sukabumi City - Bunga Ayu Ambarwati Ambarwati; Andi Mulyadi; M. Rijal Amirulloh (Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
The increasingly rapid urban development demands that local governments manage their environments adaptively, innovatively, and sustainably. One effort is through the provision and management of green open spaces, including urban forests, which serve ecological, social, educational, and aesthetic functions for the community. However, various challenges remain in their management, preventing the city forest from functioning optimally. In the Kibitay Urban Forest in Sukabumi City, various problems remain, such as damage, loss of facilities, and suboptimal maintenance. This is due to the lack of field staff, which impacts the area's function as a green open space. These conditions demonstrate the importance of implementing Dynamic Governance as a governance approach that encourages the government to adapt to dynamic changes and problems. This study aims to analyze the application of Dynamic Governance in the Management of Kibitay Urban Forest in Sukabumi City. This study used qualitative methods, with data collection techniques including observation, interviews, and documentation. The analysis was conducted based on Neo & Chen's (2007) Dynamic Governance theory, which encompasses elements of culture (long-term), capabilities (thinking ahead, thinking again, thinking across), and change. The findings indicate that dynamic governance in the management of the Kibitay Urban Forest in Sukabumi City is not yet optimal. Strengthening collaboration, learning from others, utilizing technology, and increasing management capacity are needed to realize a sustainable urban forest.